2020
DOI: 10.1038/s42003-020-0850-3
|View full text |Cite
|
Sign up to set email alerts
|

An integrative analysis of 5HTT-mediated mechanism of hyperactivity to non-threatening voices

Abstract: The tonic model delineating the serotonin transporter polymorphism's (5-HTTLPR) modulatory effect on anxiety points towards a universal underlying mechanism involving a hyperor-elevated baseline level of arousal even to non-threatening stimuli. However, to our knowledge, this mechanism has never been observed in non-clinical cohorts exhibiting high anxiety. Moreover, empirical support regarding said association is mixed, potentially because of publication bias with a relatively small sample size. Hence, how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In the same vein, although justice sensitivity was not found to be significantly associated with the permissibility of harm, it was found to be modulated by anxiety and implicit moral attitudes, both of which were intercorrelated with the 5-HTT polymorphism. These results show ecological and gene–environmental interactions and help explain why Han Chinese participants exhibit a higher proportion of the S/S genotype and a lower frequency of the L/L genotype than that observed in Caucasian populations, where the S allele was seen as conferring less susceptibility toward anxiety in Asian people ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the same vein, although justice sensitivity was not found to be significantly associated with the permissibility of harm, it was found to be modulated by anxiety and implicit moral attitudes, both of which were intercorrelated with the 5-HTT polymorphism. These results show ecological and gene–environmental interactions and help explain why Han Chinese participants exhibit a higher proportion of the S/S genotype and a lower frequency of the L/L genotype than that observed in Caucasian populations, where the S allele was seen as conferring less susceptibility toward anxiety in Asian people ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 74%
“…First, several studies have observed a significant interaction between the 5-HTT polymorphism and early-life environment on the modulation of behavior and psychological factors (including education) ( Assary et al, 2018 ), which this study did not consider. Nevertheless, this study makes use of a portion of the same sample, and utilizing the same procedures, as other studies ( Chen et al, 2020 ). Second, the sample for those homozygous for the L allele is quite small; thus, replication studies with a greater sample size are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to CTL, ASC individuals with anxiety showed significantly more negative correlations of the amygdala signal with those of the superior parietal cortex, hippocampus, and fusiform gyrus during explicit threat processing, whereas more positive correlations with the mPFC, inferior frontal cortex, temporal pole, and hippocampus, during implicit threat processing. This amygdala‐centered dysconnectivity could help explain the high level of anxiety comorbid with ASC and support the transdiagnostic neurobiological nature of anxiety (Chen et al, 2020; Herrington et al, 2016; Herrington, Maddox, McVey, et al, 2017; Top Jr. et al, 2016). On one hand, the existing significantly stronger negative couplings with the superior parietal cortex during explicit threat might explain the reduced amygdala reactivity toward explicit fear in ASCs.…”
Section: Discussionmentioning
confidence: 73%
“…Anxiety is the most prevalent co-occurring mental illness in individuals with a diagnosis for an autism spectrum disorder (ASD) (Rodgers & Ofield, 2018). Recent studies have postulated an underlying universal mechanism of anxiety which involves a hyper-or-elevated level of arousal at baseline even to nonthreatening stimuli, and that is mediated by gene expression (Chen et al, 2020;Top Jr. et al, 2016). Previous conceptualizations concerning the neuropathological changes central to the impairments in social interaction incurred by ASD individuals have emphasized amygdala dysfunction as one of its causes (Amaral et al, 2003;Baron-Cohen et al, 2000;Schultz, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…anxiety might involve a hyper-or-elevated baseline level of arousal to neutral stimuli[8,15,35,36], we further conducted detailed comparisons between explicit and implicit conditions to fearful and neutral faces (EF − IF; EN − IN), respectively. A two-way ANOVA with one within-subject variable (emotion: Neutral vs.…”
mentioning
confidence: 99%